DNA vaccines as promising immuno-therapeutics against cancer: a new insight - Shariati, Alireza; Khezrpour, Arya; Shariati, Fatemeh; Afkhami, Hamed; Yarahmadi, Aref; Alavimanesh, Sajad; Kamrani, Sina; Modarressi, Mohammad Hossein; Khani, Pouria (Frontiers in Immunology, 2025)
Cancer is one of the leading causes of mortality around the world and most of our conventional treatments are not efficient enough to combat this deadly disease. Harnessing the power of the immune system to target cancer cells is one of the most appealing methods for cancer therapy. Nucleotide-based cancer vaccines, especially deoxyribonucleic acid (DNA) cancer vaccines are viable novel cancer treatments that have recently garnered significant attention. DNA cancer vaccines are made of plasmid molecules that encode tumor-associated or tumor-specific antigens (TAAs or TSAs), and possibly some other immunomodulatory adjuvants such as pro-inflammatory interleukins. Following the internalization of plasmids into cells, their genes are expressed and the tumor antigens are loaded on major histocompatibility molecules to be presented to T-cells. After the T-cells have been activated, they will look for tumor antigens and destroy the tumor cells upon encountering them. As with any other treatment, there are pros and cons associated with using these vaccines. They are relatively safe, usually well-tolerated, stable, easily mass-produced, cost-effective, and easily stored and transported. They can induce a systemic immune response effective on both the primary tumor and metastases. The main disadvantage of DNA vaccines is their poor immunogenicity. Several approaches including structural modification, combination therapy with conventional and novel cancer treatments (such as chemotherapy, radiotherapy, and immune checkpoint blockade (ICB)), and the incorporation of adjuvants into the plasmid structure have been studied to enhance the vaccine’s immunogenicity and improve the clinical outcome of cancer patients. In this review, we will discuss some of the most promising optimization strategies and examine some of the important trials regarding these vaccines.